POTENSI EKOLOGI, POLA PENYEBARAN, DAN POLA PEMANFAATAN SERAT ALAM DALAM KAWASAN HUTAN PRODUKSI TERBATAS (HPT) GUNUNG SINONSAYANG, PROVINSI SULAWESI UTARA - Victor W. Rante Lembang; Wenny Tilaar; Terry M. Frans (Universitas Sam Ratulangi, 2015)
Abstract Rante Lembang, V.W., W. Tilaar, dan T.M. Frans, 2015. The Ecological Potential, Dispersion Patterns and Utilization Patterns of Natural Fiber in The Limited Production Forest (LPF) of Sinonsayang Mount, North Sulawesi In Province of North Sulawesi, natural fiber plants (bast plant) were found scattered either in primary forests area or secondary forests area, including in the limited production forest area (LPF) of Sinonsayang Mount. The information regards to the ecological potential, dispersion pattern, and the pattern of utilization in the region is not yet known with certainty, it is therefore need to be observed. The aim of the research was to describe the ecological potential, dispersion patterns, and the utilization patterns of natural fibers within the limited production forest (LPF) of Sinonsayang Mount, North Sulawesi. This was conducted for 2 (two) months in the limited production forest (LPF) of Sinonsayang Mount, particularly, in the area which have been used by the community as a dry land farming and the shrubs overgrown area (± 500 acres). The inventory method was used in this research, in which the plots were placed randomized using random sampling pattern (simple random sampling). The results shows, there were five (5) types of natural fibers found in the inventory field, namely: bamboo, pandanus, cotton, agave, and rosella. The bamboo population per hectare was higher than other types of natural fibers, amounting to 19 ≤ individual / ha ≤ 21, while the rosella type was found as the smallest population, about 0.08 ≤ individual / ha ≤ 0.09.. The frequency value, and the percentage value of each type of bamboo natural fiber was 0.73, and 95.66%, respectively, while the frequency value and the percentage value of each type of rosella natural fiber was the lowest, that is 0.02 and 0.04%, respectively. The dispersion pattern bamboo natural fiber types were randomly spreaded in the region, while the other types of natural fibers (pandanus, cotton, agave, and rosella) were spreaded out in groups. As for of the 5 (five) natural fibers types that found, there is only 3 types of natural fiber used by the public, viz: bamboo, pandanus, and cotton. The natural 3 fiber of bamboo was the most widely used by the community, both for personal consumption and for sale to the village market, and the market district. There were 11 forms of utilization of natural bamboo fiber by the communities surrounding the forest area for the purposes, consist of: making walls of house / cottage garden, fence, stairs, livestock pen, nesting of laying hen, ethanol refining installation of aren, to build furnace wall, medium to cook fish / pie, rice winnower, groceries bamboo shoots (young shoots), and for lalandangan. Meanwhile, the utilization of natural fibers of pandan and cotton were still limited for their own consumption as a raw material for making mats, pillows, and the fuse of the bottle lights. Keywords: Natural fibers, ecological potential, dispersion patterns, and utilization patterns